2017
DOI: 10.1123/jpah.2016-0394
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Area-Level Physical Activity Following the Implementation of a Fitness Zone in Montevideo, Uruguay

Abstract: This is the first longitudinal study on the impact of an intervention to increase the level of PA in public spaces in Uruguay. Higher intensity levels of PA and fewer sedentary people were observed after the installation of the FZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 20 publications
1
7
0
1
Order By: Relevance
“…The survey data revealed that 42% of respondents usually go to the park for exercise, which shows the importance of maximizing park infrastructure to facilitate physical activity. Similar results have been published in the literature assessing fitness zones, which have found that the placement of such infrastructure or of organized activities increases park use [14,15,17]. Such infrastructure has been implemented within the park in zones near playgrounds, where adults can potentially use the resources while the children play.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The survey data revealed that 42% of respondents usually go to the park for exercise, which shows the importance of maximizing park infrastructure to facilitate physical activity. Similar results have been published in the literature assessing fitness zones, which have found that the placement of such infrastructure or of organized activities increases park use [14,15,17]. Such infrastructure has been implemented within the park in zones near playgrounds, where adults can potentially use the resources while the children play.…”
Section: Discussionsupporting
confidence: 66%
“…Trojan Park has implemented Fitness zones, which are free outdoor fitness equipment stations placed in local parks—one of the newer strategies to promote MVPA for a variety of ages [12]. Many countries in Asia, Europe, South America and Australia have already implemented fitness zones in parks [13,14,15,16,17,18]. Cohen et al define fitness zones as “easy to use outdoor gyms consisting of durable, weather-, and vandal resistant exercise equipment for strength training and aerobic exercise [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of males found in this study (60.3%) has been showed in other studies. Joseph and Maddock 8 (54.9%), Evenson et al 7 (57.2%), Parra et al 15 (56%), Hino et al 14 (63.1%), and Del Campo Vega 16 (56%) found a similar trend to different studies from the United States; however, in other countries like China, Taiwan, and Australia, the distribution by sex was higher for females 8 because the parks represent a meeting place for PA and socialization with an increased perception of safety.…”
Section: Discussionmentioning
confidence: 98%
“…In the body of literature, only Brazil (in the cities of Curitiba 14 and Recife 15 ) and Uruguay (Montevideo 16 ) have published patterns of park use. In Colombia, a recent publication shows the effects of…”
mentioning
confidence: 99%